Insect pest and plant disease management in horticultural crop production: recent insights provide opportunities for improved control - Ojiambo, Peter S. (Frontiers in Horticulture, 2025)
With the world population projected to increase to approximately 8 billion people by 2030, tremendous efforts are needed to produce enough food to feed the population with a decreasing land available for agricultural production. Horticultural crops, characterized by very diverse production systems, continue to play a significant role in food security and safety. However, plant pests and plant diseases continue to negatively impact the production of healthy and safe food in horticultural cropping systems, by affecting produce quality, quantity, and safety. Furthermore, the emergence and re-emergence of pests and pathogens coupled with the rapid development of resistance to available pesticides further exacerbate the challenges of pest and disease control in horticultural systems. Given the recognized need to mitigate climate-change risks, novel pest and disease management strategies are required to achieve net-zero emissions for more sustainable horticultural production. This perspective highlights some recent research insights that could provide opportunities for the improved management of insect pests and plant diseases in horticultural crop production systems.